Respuesta :
Answer:
x^2 + 11x + k = 0
(-4) ^2 + 11 (-4) + k = 0
16 - 44 + k = 0
-28 + k = 0
K = 28
Hope Helpful ~
Answer: K = 28
Step-by-Step Explanation:
x^2 + 11x + K = 0; where x = -4
Substitute the value of ‘x’ in Equation :-
= (-4)^2 + 11(-4) + K = 0
= 16 + -44 + K = 0
= -44 + K = -16
=> K = -16 + 44 = 28
Therefore, K = 28
Step-by-Step Explanation:
x^2 + 11x + K = 0; where x = -4
Substitute the value of ‘x’ in Equation :-
= (-4)^2 + 11(-4) + K = 0
= 16 + -44 + K = 0
= -44 + K = -16
=> K = -16 + 44 = 28
Therefore, K = 28